2018
DOI: 10.7150/jbji.22192
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance profiles of deep surgical site infections in hip hemiarthroplasty; comparing low dose single antibiotic versus high dose dual antibiotic impregnated cement

Abstract: Objectives: The incidence of fractured neck of femur (FNOF) is increasing yearly. Many of these patients undergo hip hemiarthroplasty. High dose dual-antibiotic cement (HDDAC) has been shown to reduce rates of deep surgical site infection (SSI) when compared to the current standard low dose single-antibiotic cement (LDSAC) in a quasi-randomised controlled trial. Some concerns exist regarding the use of HDDAC and the development of antibiotic resistance. We reviewed cases of infection in LDSAC and HDDAC bone ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 13 publications
(19 reference statements)
2
20
0
Order By: Relevance
“…21,22 Of most clinical importance was the recent finding that bacteria found in PJI -even if resistant to gentamicin -did not show cross-resistancies to other antibiotics commonly used for antibiotic treatment. 23 Resistance patterns in Nordic countries…”
Section: Albc Use and Antimicrobial Resistance Developmentmentioning
confidence: 99%
“…21,22 Of most clinical importance was the recent finding that bacteria found in PJI -even if resistant to gentamicin -did not show cross-resistancies to other antibiotics commonly used for antibiotic treatment. 23 Resistance patterns in Nordic countries…”
Section: Albc Use and Antimicrobial Resistance Developmentmentioning
confidence: 99%
“…In a very recent analysis within a large clinical trial designed to compare the infection rates in neck-of-femur fracture patients as a function of the antibiotic-loaded bone cement used for the fixation of the hemiprosthesis, Tyas et al reviewed the cases of deep surgical site infections with regard to the causative pathogens and their antibiotic resistance profiles. 39 It was found that the reduction in deep infection cases was such in patients receiving a high dose antibiotic-loaded cement (HDAC) (infection rate: 1.2% in HDAC group = bone cement with 1 g gentamicin and 1 g clindamycin) as compared with a low dose antibiotic cement (LDAC) (infection rate: 3.4% in LDAC group = bone cement with 0.5 g gentamicin; p = 0.003) that there was a trend towards a lower rate of resistance with the use of HDAC. The authors therefore concluded that the concomitant prophylactic use of two antibiotics in the cement did not drive antibiotic resistant infections (see Table 2).…”
Section: Use Of Local Antibiotics and Antibiotic Resistance Developmentmentioning
confidence: 99%
“… 18 The concern with widespread use of high dose dual ALBC is increased cost, and the risk of increased antibiotic resistant periprosthetic joint infections, although published data on the later appears reassuring. 16 There is also a theoretical risk of systemic toxicity, though there is little to no compelling data supporting this concern. 19 …”
Section: Introductionmentioning
confidence: 99%